2001
DOI: 10.3168/jds.s0022-0302(01)74602-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Directed Compensatory Growth Enhances Heifer Development and Lactation Potential

Abstract: The objectives of this study were 1) to examine the interactive influence of a compensatory nutrition regimen and lasalocid supplementation on dairy heifer growth performance and 2) to document the extent to which compensatory growth sustains lactation potential over the first two lactation cycles. Twelve Holstein heifers, weighing an average of 160 kg (about 6 mo of age) were randomly assigned to treatments arranged in a 2 x 2 factorial design. Treatment variables were two dietary regimens (control and stair-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 24 publications
7
43
2
1
Order By: Relevance
“…The authors claimed that gains above this level concentrate more quantity of fat tissue in the mammary gland, reducing the milk production at the first lactation and also at the subsequent ones. Nevertheless, it must be considered that in other studies, no negative effect from feeding was observed in the pre-pubertal period and during milk production ( VAN AMBURGH et al, 1998;SEJRSEN et al 2000;FORD;PARK, 2001). In this way, the weight gain obtained in this study (0.875 kg day -1 ) may not cause problems in future lactations of these heifers.…”
Section: Resultssupporting
confidence: 44%
“…The authors claimed that gains above this level concentrate more quantity of fat tissue in the mammary gland, reducing the milk production at the first lactation and also at the subsequent ones. Nevertheless, it must be considered that in other studies, no negative effect from feeding was observed in the pre-pubertal period and during milk production ( VAN AMBURGH et al, 1998;SEJRSEN et al 2000;FORD;PARK, 2001). In this way, the weight gain obtained in this study (0.875 kg day -1 ) may not cause problems in future lactations of these heifers.…”
Section: Resultssupporting
confidence: 44%
“…Digestive and metabolic adaptations in this rebound period are effective within few days (Hoch et al, 2003), showing the reactivity of the organism to benefit from an improvement in its nutritional conditions. Such a strategy can be successfully applied to dairy heifers (Ford and Park, 2001). …”
Section: Effects Of Feeding Practices In Producing Animalsmentioning
confidence: 99%
“…This may reduce feed costs by making use of compensatory growth mechanisms during the well-fed periods. For example, Ford and Park (2001) trialled a three-step regime between 6 months and first calving in dairy heifers. This was said to benefit mammary development and milk production in the first and second lactations, but with only four animals per group.…”
Section: Nutrition and Growth Ratementioning
confidence: 99%